EVALUASI KONSEP KAWASAN TRANSIT ORIENTED DEVELOPMENT (TOD) STASIUN CISAUK, KECAMATAN CISAUK, KABUPATEN TANGERANG, BANTEN. (STUDI KASUS STASIUN CISAUK, KECAMATAN CISAUK, KABUPATEN TANGERANG) - Beryllium Safiullah Ahmad; Sylvie Wirawati; B. Irwan Wipranata (Jurusan Arsitektur dan Perencanaan, 2021)
City development with the concept of Transit Oriented Development (TOD) is a city development that relies on mass transportation modes, the concept of Transit Oriented Development (TOD) in the City, namely as a buffer for the capital against cities that are around the city center. Recently, Transit Oriented Development (TOD) has become a solution to integrate housing with mass transportation so as to facilitate access to the capital, in the development of Transit Oriented Development (TOD) there are special standards that follow standard assessment criteria both nationally and internationally. Transit Oriented Development Cisauk Station is one of the Transit Oriented Developments being developed in Tangerang Regency, as well as the Capital City Supporting City. The purpose of this study is to analyze the suitability of the development of the Transit Oriented Development (TOD) area of Cisauk Station, both based on the Tangerang Regency Spatial Planning (RTRW) Regulations 2011-2031 and based on the criteria of the Standard Institute for Transportation and Development Policy (ITDP) to determine the suitability of the Transit Oriented area. Development (TOD) Cisauk Station. Based on the results of the evaluation of theanalysis scorecard using comparative qualitative methods resulted in the suitability of theProject of Transit Oriented Development (TOD)Cisauk Station against theof criteriathe Standard Institute For Transportation and Development Policy (ITDP) with aspects of walking/walking, cycling/cycle, connecting/connecting, public transportation /transit, mixing, compressing, compacting, and shifting, then the Transit Oriented Development (TOD) of Cisauk Station has met the standard criteria for Transit Oriented Development TOD) and has a percentage value of 55% – 69% from 100% assessment. The researcher knows that the results of the evaluation of the Transit Oriented Development (TOD) Cisauk Station are included in the category of theassessment class criteria Bronze, this result was obtained by the researchers by comparing the research data and the assessment criteria based on the International Institute For Transportation and Development Policy (ITDP). Keywords: Evaluation; Transit Oriented Development; Criteria Standard Institute For Transportation and Development Policy (ITDP); Cisauk Station. AbstrakPengembangan kota dengan konsep Transit Oriented Development (TOD) merupakan pengembangan kota yang bertumpu pada moda transportasi massal, konsep Transit Oriented Development (TOD) di Kota yaitu sebagai penyangga Ibukota terhadap kota – kota yang berada di sekitar pusat kota. Belakangan ini Transit Oriented Development (TOD) menjadi solusi untuk mengintergrasikan hunian dengan transportasi massal sehingga memudahkan akses menuju ibukota, dalam pengembangan Transit Oriented Development (TOD) terdapat standar khusus yang mengikuti kriteria standar penilaian baik secara nasional maupun internasional. Transit Oriented Development Stasiun Cisauk merupakan salah satu Transit Oriented Development yang sedang dikembangkan di Kabupaten Tangerang, sekaligus sebagai Kota Penyangga Ibukota. Tujuan penelitian ini untuk menganalisis kesesuaian pengembangan kawasan Transit Oriented Development (TOD) Stasiun Cisauk baik berdasarkan Peraturan Rencana Tata Ruang Wilayah (RTRW) Kabupaten Tangerang 2011 – 2031 maupun berdasarkan kriteria Standard Institute for Transportation and Development Policy (ITDP) untuk mengetahui kesesuaian kawasan Transit Oriented Development (TOD) Stasiun Cisauk. Berdasarkan hasil dari evaluasi analisis scorecard dengan menggunakan metode kualitatif komparatif menghasilkan kesesuaian Proyek Transit Oriented Development (TOD) Stasiun Cisauk terhadap kriteria Standard Institute For Transportation and Development Policy (ITDP) dengan aspek berjalan/walk, bersepeda/cycle, menghubungkan/connect, angkutan umum/transit, pembauran/mix, memadatkan/densify, merapatkan/compact, dan beralih/shift, maka Transit Oriented Development (TOD) Stasiun Cisauk sudah memenuhi kriteria standar Transit Oriented Development TOD) dan memiliki nilai persentase 55% – 69% dari 100% penilaian. Peneliti mengetahui bahwa hasil evaluasi Transit Oriented Development (TOD) Stasiun Cisauk masuk dalam katagori kriteria kelas penilaian Bronze, hasil ini di dapatkan oleh peneliti dengan mengkomparatifkan data hasil penelitian dan kriteria penilaian berdasarkan International Institute For Transportation and Development Policy (ITDP).